The Impact of Phytogenic Feed Additives on Growth Performance, Carcass Traits and Immune Response in Broilers under Summer Stress - , T.Mounika, M.Hanumanth Rao, T. Srilatha; B. Prakash; Srinivas, Gurram; Mendu Mounika; Ratna , Supriya; K. Sushmasri; Tulasi Ravula (Indian Journal of Animal Nutrition, 2025)
This study was conducted to evaluate the effect of some phytogenic feed additives (PFA) on growth performance, carcass parameters and immune response in broiler chicken during summer stress. A total of 240-day-old commercial male broiler chicks were randomly allotted to either of four dietary treatments with twelve replications of five birds each and reared in battery brooder up to 42 days of age. The treatments consist of a control diet (CD), CD supplemented with PFA-I containing clove and eucalyptus essential oil @ 25g/100kg, PFA-II containing blend of oregano, cinnamon, citrus peel and fructo-oligosaccharides @10g/100kg and PFA-III containing amla and linseed powder @10g/100kg. At the end of 42 days, the results indicated that body weight gain, feed intake, feed conversion ratio and carcass parameters were significantly (P<0.05) improved in the phytogenic supplemented groups. However, humoral immunity (NDV titer) and cell-mediated immune response to PHA-P were not affected by different phytogenic supplementation.